Effect of Thermal Power Station Effluent on Morphometrical and Biochemical Changes of Groundnut (Arachis hypogaea (L)) Variety VRI-5 Seedlings - M . Krishnaveni1, S.James1, M. Noorunisa Begam1 , P.S. Sharavanan2*, (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Rapid industrialization lead to high discharge of industrial effluent which may pollute ecosystem. Discharge of fly-ash from thermal, electric and atomic power plant and coal washries from lignite mining are serious source of water pollution which severely polluted paravanaru river, Neyveli, Cuddalore district,Tamil Nadu. The physico-chemical analysis of the thermal power station effluent showed high alkalinity, BOD , COD values and more total dissolved salts. EffectÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â of various concentration (viz.10%, 25%, 50%, 75% and 100%) of the effluent was tested on seed germination and biochemical changes of groundnut (Arachis hypogaea) seedlings. Eichhornia crassipes (water hyacinth) and Pistia stratiotes (water lettuce) which have been employed for waste water treatment for 48 hours (B.T.E). The results indicate that the lower concentration there is a significant increase in the percentage of seed germination, growth parameters and pigment contents. But it decreased with theÂ increase of thermal power effluent above 25%. Therefore the 25% effluent (B.T.E) dilution was found to be most suitable which can be used as a liquid fertilizer. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">— <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> 1Department of Botany, Bharathiyar University, Coimbatore. Tamil NaduÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â 2Department of Botany, Annamalai University, Annamalai Nagar, Tamil Nadu —- <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> Please Cite This Article As: Â M. Noorunisa Begam, P.S. Sharavanan, M . Krishnaveni, S.James. 2010. Effect of Thermal Power Station Effluent on Morphometrical and Biochemical Changes of Groundnut (Arachis hypogaea (L)) Variety VRI-5 Seedlings. J. Ecobiotechnol. 2(5):31-35. Â